Lanthanoid Complexation by a Tris‐Tetrazole‐Functionalised Calix[4]arene. Issue 34 (28th October 2016) - D'Alessio, Daniel; Skelton, Brian W.; Sobolev, Alexandre N.; Krause‐Heuer, Anwen M.; Fraser, Benjamin H.; Massi, Massimiliano; Ogden, Mark I.
Abstract : The synthesis and characterization of 5, 11, 17, 23‐tetra‐ tert ‐butyl‐25‐hydroxy‐26, 27, 28‐tris(tetrazol‐5‐ylmethoxy)calix[4]arene is reported. Purification of the macrocycle required the use of preparative HPLC techniques. The macrocycle was found to be a poorer ligand for complexation of lanthanoid cations than the bis(tetrazole) analogue, but somewhat more effective than the tetrakis(tetrazole)‐substituted derivative. Two metal complexes of the tris(tetrazole)–calixarene were structurally characterised. A polymeric sodium salt of the tris(tetrazole)–calixarene was isolated from a solution containing yttrium and a sodium acetate buffer. A praseodymium complex was isolated in the presence of an ammonium acetate buffer, where the calixarene acts as a unidentate ligand, bound to the metal atom through one tetrazole N‐atom. Increasing the amount of buffer resulted in the crystallisation of a metal‐free ammonium salt of the calixarene. Abstract : Favourable intramolecular interactions are presumed to be the cause of this macrocyclic ligand binding in a unidentate manner to a sodium coordination polymer and a praseodymium cation.